Institutional investors and corporate restructuring : effects of ownership structure and activism - Lee, Hwee Kiang (2008)
This project examines the influence of institutional investors on corporate restructuring. Our study addresses this question by extending prior empirical research on the influence of different types of institutional investors on corporate restructuring. We also study the impact of activism, instead of institutional ownership alone, on corporate restructuring.